Islamic Law Overview on Implementation of Murabahah Bil Wakalah on Multi-Purpose Financing Products - Mualim; Hendra Karunia Agustine; Annisa Hariyani (Journal of Applied Business, Taxation and Economics Research, 2021)
This study aims to examine the implementation of Murabahah bil Wakalah on multipurpose financing products in a review of Islamic Law. The research method used in this research is field research (field research). The types and sources of data in this study used primary and secondary data. Data collection techniques through interviews, observation, and documentation. The data obtained in this study are conclusions from various processes in qualitative research. Starting from data collection, selecting appropriate data, presenting data and then concluding.The results of this study are murabahah bil wakalah contracts in multipurpose financing at BPRS HIK Parahyangan, murabahah contracts are carried out simultaneously with wakalah contracts. Where the murabahah contract is carried out at the beginning to determine the selling price, the agreed profit, and the installment period.